Unmasked and Exposed: the Impact of COVID-19 on the Youth Custodial Estate : A Compelling Case for Ideological Change - Smithson, Hannah (The British journal of criminology, 2024)
The impact of the COVID-19 pandemic on custodial institutions has been the subject of intense scrutiny. During the pandemic, many international jurisdictions failed to develop clear and child-focussed plans for the management of children in custody, instead relying on strategies developed for adult populations. Presenting the findings from the United Kingdom’s (England Wales) first empirical in-depth exploration of the impacts of COVID-19 on children at each stage of the Youth Justice System, this article discusses the devastating effect on incarcerated children. The pandemic exacerbated existing failures in the children’s secure estate, eradicated children’s rights and exposed children to increased vulnerabilities. We present an urgent need for a fundamental ideological reconsideration of the purpose of custody for children.